Effectiveness of mahogany seed flour (Swietenia macrophylla) as a bioinsecticide against mortality of Sitophilus zeamais motsch in post-harvest grains - Eka Nurriza Khairunnisa; Ira Gusti Rian; Nia Boru Ritonga; Raudhatus Saadah; Madyasta Anggana Rarassari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Research has been conducted on the effect of giving Mahogany seed meal (Swietenia macrophylla) on the mortality of the beetle Sitophilus zeamais Motsch. The method used is an experimental method with a complete randomized design consisting of 6 treatments and 4 repeats. The treatment consisted of controls A0 (0%), A1 (2%), A2 (4.8%), A3 (7.4%), A4 (13.0%), and A5 (17.4%). Mahogany seed flour with a concentration in each treatment was mixed with granulated corn to a weight of 50 grams, placed 20 Sitophilus zeamais beetles and observed for 24, 48, 72 and 96 hours. Data were analyzed by anava calculation and BJND test at 24-hour observation, BNT test at 48-hour observation and BNJ test at 72- and 96-hour observations. The concentration of 17.4% gave the greatest beetle mortality effect, namely 75% at 24 hours, 81.25% at 48 hours, 91.25% at 72 hours and 100% at 96 hours from the number of 20 beetles tested. This study also produced KL50 values for mahogany seed flour, namely 11.90% at 24 hours, 10.41% at 48 hours, 8.69% at 72 hours and 7.23% at 96 hours.